2017
DOI: 10.1016/j.celrep.2016.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Brca1 Mutations Differentially Reduce Hematopoietic Stem Cell Function

Abstract: BRCA1 is a well-known DNA repair pathway component and a tissue-specific tumor suppressor. However, its role in hematopoiesis is uncertain. Here we report that a cohort of patients heterozygous for BRCA1 mutations experienced more hematopoietic toxicity from chemotherapy than those with BRCA2 mutations. To test whether this reflects a requirement for BRCA1 in hematopoiesis, we generated mice with Brca1 mutations in hematopoietic cells. Mice homozygous for a null Brca1 mutation in the embryonic hematopoietic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 53 publications
6
37
0
Order By: Relevance
“…There was no significant difference in BRCA status by regimen, time, or time squared interaction. Blood count patterns differed by chemotherapy regimen and within regimen by drug and dose intensity (Supporting Information [13][14]. Patterns in mutation carriers closely followed those in wild-type patients.…”
Section: Change In Blood Count Parameters Over Timementioning
confidence: 97%
See 1 more Smart Citation
“…There was no significant difference in BRCA status by regimen, time, or time squared interaction. Blood count patterns differed by chemotherapy regimen and within regimen by drug and dose intensity (Supporting Information [13][14]. Patterns in mutation carriers closely followed those in wild-type patients.…”
Section: Change In Blood Count Parameters Over Timementioning
confidence: 97%
“…Reported toxicities included more frequent dose‐limiting neutropenia and neutropenic fever, cases of therapy‐related leukemia, and lower baseline blood counts. However, conclusions were limited by small sample size, lack of a comparable control population, and/or inability to evaluate those with BRCA1 vs BRCA2 mutations separately . Thus, we performed a multicenter, retrospective, matched cohort study to compare the frequency, severity, and timing of hematologic toxicities occurring throughout the multicycle curative intent chemotherapeutic regimens for breast cancer in women with and without an inherited BRCA1 or BRCA2 mutation.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that some mice die during late embryonic development, when hematopoietic organs are developed and hematopoietic stem cells transit from fetal liver to fetal bone marrow [40]. Recent studies have shown that BRCA1 is important for hematopoiesis [41,42]. Therefore, hematopoietic defects might account for the death of some Brca1 −/− ;Trp53bp1 −/− embryos during late embryonic development.…”
Section: Mmej Potentially Contribute To the Survival Of Brca1-53bp1 Dmentioning
confidence: 99%
“…Notably, in the absence of a functional Fanconi anemia repair pathway, LT-HSCs show high rates of bone-marrow failure and cell death in response to stressinducing stimuli and markedly lower repopulating capacity compared to the wild-type cell counterparts [19]. Interestingly, Brca1 conditional deletion from embryonic hematopoietic cells determines pancytopenia and total loss of HSCs in the adult mice, while heterozygosity for a Brca1 mutant allele results in a modest yet significant decrease in white blood cells, as well as in a deficit in HSC self renewal potential, as assessed by serial bone-marrow transplantation [21], again emphasizing the role of DDR in HSC maintenance.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 99%